If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + 6m + 3m + 6m + -7 = 0 Reorder the terms: -7 + 4m + 6m + 3m + 6m = 0 Combine like terms: 4m + 6m = 10m -7 + 10m + 3m + 6m = 0 Combine like terms: 10m + 3m = 13m -7 + 13m + 6m = 0 Combine like terms: 13m + 6m = 19m -7 + 19m = 0 Solving -7 + 19m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 19m = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 19m = 0 + 7 19m = 0 + 7 Combine like terms: 0 + 7 = 7 19m = 7 Divide each side by '19'. m = 0.3684210526 Simplifying m = 0.3684210526
| y^2+3y-18= | | 5(2)+2y=6 | | 14x-14=98 | | 2x^2=-98 | | (3-12x^2+4x^4)=0 | | 2x-x=54 | | 2x^3-8x=0 | | 7x+3-5x-1=-26 | | 2(3)+3y=6 | | -15x-59=117-4x | | 6x+4=96 | | P+12=2(P+P+3) | | -4-4y=-12 | | -4-4y=12 | | x^2-7x= | | -4(-1)+y=5 | | -4x+y=5 | | -15x-35=25-11x | | 1.296/.27= | | -5(x+10)+403=32+21 | | x+4=-4x+9 | | (2x+7)(3x^2-14x+15)=0 | | 2+y=-6 | | 5=2-3x-1 | | 8x+12y=3840 | | -15x+4=139 | | 4x^3-16=0 | | 5(2z-1)4(z+5)=2(z+1) | | 14x-172=158+4x | | 37=6x-11 | | r(r-6)=16 | | 4u^2+9u=-2 |